DCE-MRI Quantitative Parameters as Predictors of Treatment Response in Patients With Locally Advanced Cervical Squamous Cell Carcinoma Underwent CCRT - Liu, Bing; Sun, Zhen; Ma, Wan-Ling; Ren, Jing; Zhang, Guang-Wen; Wei, Meng-Qi; Hou, Wei-Huan; Hou, Bing-Xin; Wei, Li-Chun; Huan, Yi; Zheng, Min-Wen (Frontiers in Oncology, 2020)
Purpose: To evaluate quantitative parameters of dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) in predicting treatment response to concurrent chemoradiotherapy (CCRT) for patients with locally advanced cervical squamous cell carcinoma (LACSC). Methods and materials: LACSC patients treated with CCRT had DCE-MRI before (e0) and after 3 days of treatment (e3). Pharmacokinetic modeling with a user vascular input function was used for the quantitative measurements. Endothelial transfer constant (Ktrans), reflux rate (Kep), fractional extravascular extracellular space volume (Ve) and fractional plasma volume (Vp) were calculated and percentage changes ΔKtrans, ΔKep,ΔVe,ΔVp were computed. The correlations of these measurements with tumor regression rate were evaluated. The value of these parameters on predicting treatment outcome was calculated by receiver operating characteristic (ROC) curve. Multivariate logistic regression analysis was conducted to find the independent variables. Results: Ktrans-e0, Kep -e0, ΔKtrans and ΔVe were positively corelated with tumor regression rate. Mean values of Ktrans-e0, Ktrans-e3, ΔKtrans and ΔVe were higher in non-residual tumor group than residual tumor group and were independent prognostic factors for predicting residual tumor occurrence. Ktrans-e3 showed highest area under the curve (AUC) for treatment response prediction. Conclusions: Quantitative parameters at e0 and e3 from DCE-MRI could be used as potential indicators for predicting treatment response of LACSC.